Understanding the anomalous thermal behavior of Σ3 grain boundaries in a variety of FCC metals. (December 2018) - Chesser, Ian; Holm, Elizabeth
Abstract: We present a case study of the complex temperature dependence of grain boundary mobility. The same general incoherent twin boundary in different FCC metals is found to display antithermal, thermal, and mixed mobility during molecular dynamics synthetic driving force simulations. A recently developed energy metric known as the generalized interfacial fault energy (GIFE) surface is used to show that twin boundaries moving in an antithermal manner have a lower energetic barrier to motion than twin boundaries moving in a thermally activated manner. Predicting the temperature dependence of grain boundary motion with GIFE curves stands to accelerate research in grain boundary science. Graphical Abstract: